Tris(pentafluorophenyl)borane‐Catalyzed Reactions of Siloxanes: A Combined Experimental and Computational Study. Issue 33 (5th September 2017) - Mathew, Jomon; Eguchi, Katsuya; Nakajima, Yumiko; Sato, Kazuhiko; Shimada, Shigeru; Choe, Yoong‐Kee
Abstract : The reaction of 1, 1, 3, 3‐tetramethyldisiloxane with 1‐octene as a model reaction of silicone curing catalyzed by B(C6 F5 )3 resulted in the redistribution of the disiloxane into dimethylsilane and cyclic oligosiloxanes, and the subsequent hydrosilylation reaction of dimethylsilane afforded dimethyldioctylsilane. To obtain insights into the reaction mechanism and possibility alter the reaction pathway to favor the hydrosilylation over the redistribution, mechanistic analysis of the reaction between a hydrosiloxane (1, 1, 3, 3‐tetramethyldisiloxane, silox‐H) and a vinylsiloxane (1, 1, 3, 3‐tetramethyl‐1, 3‐divinyldisiloxane, silox‐vin) in the presence of B(C6 F5 )3 was performed through density functional theory calculations. The results of the calculations indicate that the activation of a Si–H bond in silox‐H by B(C6 F5 )3 initiates the reaction to form the B(C6 F5 )3 –silox‐H complex with a Lewis acidic silicon atom and a hydridic hydrogen atom. The B(C6 F5 )3 –silox‐H complex can undergo two different reaction pathways, that is, trisiloxane formation and the hydrosilylation of silox‐vin by silox‐H. The trisiloxane formation involves trisilyloxonium ions as intermediates and can lead to either the homotrisiloxane of silox‐H or a mixed trisiloxane of silox‐H and silox‐vin. The energetics of the reaction pathways predict the preference of trisiloxane formation over hydrosilylation, and the fine tuning of the steric and electronic natures of the substrates could alter the thermodynamic and kinetic favorability. Abstract : The results of a combined experimental and computational study on the reaction between a hydrosiloxane (1, 1, 3, 3‐tetramethyldisiloxane, silox‐H) and a vinylsiloxane (1, 1, 3, 3‐tetramethyl‐1, 3‐divinyldisiloxane, silox‐vin) in the presence of B(C6 F5 )3 are reported. The theoretical results predict the preference of trisiloxane formation over hydrosilylation for this reaction.